Autism and adolescence--the way I see it : what teens and adults need to know - Grandin, Temple (Future Horizons, 2024)
"Dr. Temple Grandin draws on her hard-won experience to deliver an essential guidebook for guiding and nurturing autistic youth. She gets to the real issues of autistic adolescents--the ones parents, teachers, and individuals on the spectrum face every day."--